Laparoscopic surgery versus radiofrequency ablation for the treatment of single hepatocellular carcinoma ≤3 cm in the elderly: a propensity score matching analysis. Issue 1 (January 2022) - Conticchio, Maria; Delvecchio, Antonella; Ratti, Francesca; Gelli, Maximiliano; Anelli, Ferdinando M.; Laurent, Alexis; Vitali, Giulio C.; Magistri, Paolo; Assirati, Giacomo; Felli, Emanuele; Wakabayashi, Taiga; Pessaux, Patrick; et al.
Abstract: Background: Laparoscopic liver resection (LLR) and radiofrequency ablation (RFA) represented potential treatments for patients with a single hepatocellular carcinoma (HCC) smaller than 3 cm. As the aging population soared, our study aimed to examine the advantage/drawback balance for these treatments, which should be reassessed in elderly patients. Methods: A multicentric retrospective study compared 184 elderly patients (aged >70 years) (86 patients underwent LLR and 98 had RFA) with single ≤3 cm HCC, observed from January 2009 to January 2019. Results: After propensity score matching (PSM), the estimated 1- and 3-year overall survival rates were 96.5 and 87.9% for the LLR group, and 94.6 and 68.1% for the RFA group (p = 0.001) respectively. The estimated 1- and 3-year disease-free survival rates were 92.5 and 67.4% for the LLR group, and 68.5 and 36.9% for the RFA group (p = 0.001). Patients with HCC of anterolateral segments were more often treated with laparoscopic resection (47 vs. 36, p = 0.04). The median operative time in the resection group was 205 min and 25 min in the RFA group (p = 0.01). Length of hospital stay was 5 days in the resection group and 3 days in the RFA group (p = 0.03). Conclusion: Despite a longer length of hospital stay and operative time, LLR guarantees a comparable postoperative course and a better overall and disease-free survival in elderly patients with single HCC (≤3 cm), located in anterolateral segments.